Correlación entre los periodos de inducción oxidativa y métodos sensoriales para determinar el umbral de aceptación en aceites vegetales comestibles - Molina Quijije, Génesis Nataly (2021)
In the oil and grease industry, it is essential to study the shelf life based on oxidative stability, creating the challenge of being able to estimate this information more accurately. The objective of this work was to determine the threshold of acceptance of edible vegetable oils by instrumental sensory methods and human perception, after subjecting them for different periods of time to an accelerated oxidation in Rancimat. Refined and deodorized samples of sunflower and soybean were used to determine the induction periods. The analysis temperature for the treatments was 110°C, taking samples at conductivities 10, 20, 30 and 40 μS / cm, the characterization of volatile organic compounds (VOC) was carried out by means of static volatile head gas chromatography, the Sensory evaluation with a panel of untrained tasters, a block design was applied and the correlation was carried out using simple linear regression of VOCs and the sensory method. It was observed that there are correlations of the VOCs of the conductivities and the results of the sensory panel. The R² of the concentration of volatile compounds for each experimental unit was 0.8411, 0.8400 and 0.8397 for sunflower and 0.7298, 0.7923 and 0.7978 for soybean. The conductivity of 10 μS / cm was identified for both oils as the most acceptable treatment rated by the panelists, highlighting that the conductivity of 40 μS / cm showed acceptability despite being the treatment with the highest oxidative level.